Komunikasi dan Motif Penggunaan Toah Masjid Kecamatan Depok Yogyakarta - Alen Manggola (JOPPAS: Journal of Public Policy and Administration Silampari, 2020)
The purpose of this study was to determine the communication and motives for the use of Toah Masjid, Depok Yogyakarta District. This study uses qualitative research using description analysis methods. The theory used is a two-stage communication model and a phenomenological theory put forward by Alfred Schutz. The results of this study indicate that the application of guidelines for the use of loudspeakers in the mosque can be identified through two-stage communication that is established between the Regional Office with the instructor and from the instructor to the mosque Takmir. Two-stage communication using Interpersonal Communication and Social Communication. The important role of policy counselors as gatekeepers and opinion leaders in public policy socialization. Conclusion, the motive of using mosque loudspeakers to the outside other than the call to prayer in several mosques in the Sub-district of Depok, such as reading prayers, dhikr, prayers, prayers and announcements because they have not received policy socialization, no one has questioned their use, to attract the attention of others. Keywords: Communication, Motives, Mosque Toah